Open port – closed residential quarters? Urban structural transformation in the metropolitan area of Valparaíso, Chile - Borsdorf, Axel; Hidalgo, Rodrigo (ERDKUNDE, 2008)
In recent decades the construction of residential quarters with restricted access in Chilean cities has increased dramatically and has been the subject of many surveys. However, most of these studies focused on the metropolitan area of the country’s capital, Santiago de Chile. The country’s second largest agglomeration, including the urban areas of Valparaíso and Viña del Mar, is the subject of this study. In Valparaíso, known as Chile’s “Gateway to the World”, the contradiction between an open port and an open-minded, liberal population and the impact of globalisation, resulting in gated com-munities and restricted areas is one of the most significant characteristics of urban development in recent decades. The new structures of fragmentation that can be found in Santiago de Chile and all other Latin-American metropolises affected by globalisation, neoliberalism, and post-modern urban development, also emerged in the Metropolitan Area of Valparaíso. Caused by the natural setting and amenities (coastline, sea view) in Valparaíso, the traditional bipolarity of the rich and the poor city has remained to a certain degree. The wealthy live in high-rise buildings near the coast, the middle and lower classes in the hinterland, preferring single household dwellings of standardised design. It is only in the distribution of central functions that a tendency towards fragmented structures comes to the fore.